Impacts of ovarian reserve on conservative treatment for endometrial cancer and atypical hyperplasia - Wu, Pengfei; Shan, Weiwei; Xue, Yu; Wang, Lulu; Liu, Sijia; Chen, Xiaojun; Luo, Xuezhen (Frontiers in Endocrinology, 2024)
Real-world data indicated that some endometrial atypical hyperplasia (EAH) and early endometrial carcinoma (EEC) patients of fertility preservation had a normal ovarian reserve, while some had a decreased ovarian reserve (DOR). This study was designed to investigate the effect of baseline ovarian reserve on the treatment of EAH and EEC patients who ask for preservation of fertility. Methods: This was a prospective cohort study conducted at a single universityaffiliated fertility center. A total of 102 EAH and EEC patients who received fertilitypreserving treatment between March 2019 and August 2020 were included and divided into a DOR group (n=22) and a non-DOR group (n=80).The 32-week CR rate of the non-DOR group was significantly higher than that of the DOR group (60.3% vs. 33.3%, P =0.028). The DOR group had a longer treatment duration to achieve CR than the non-DOR group (40.07 vs. 29.71 weeks, P=0.008, HR: 0.54, 95% CI: 0.36-0.86). Multivariate logistic regression analyses demonstrated that DOR (OR: 0.35, 95% CI: 0.13-0.99, P=0.049) and BMI ≥25 kg/m 2 (OR: 0.40, 95% CI: 0.17-0.92, P=0.031) were negatively associated with 32-week CR. Conclusions: Decreased baseline ovarian reserve is negatively correlated with the efficacy of fertility-preserving treatment in EAH and EEC patients, as this group has a lower CR rate and a longer treatment duration to achieve CR than those without DOR.